ECG T‐Wave Morphologic Variations Predict Ventricular Arrhythmic Risk in Low‐ and Moderate‐Risk Populations - Julia Ramírez; Antti Kiviniemi; Stefan van Duijvenboden; Andrew Tinker; Pier D. Lambiase; Juhani Junttila; Juha S. Perkiömäki; Heikki V. Huikuri; Michele Orini; Patricia B. Munroe (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Early identification of individuals at risk of sudden cardiac death (SCD) remains a major challenge. The ECG is a simple, common test, with potential for large‐scale application. We developed and tested the predictive value of a novel index quantifying T‐wave morphologic variations with respect to a normal reference (TMV), which only requires one beat and a single‐lead ECG. Methods and Results We obtained reference T‐wave morphologies from 23 962 participants in the UK Biobank study. With Cox models, we determined the association between TMV and life‐threatening ventricular arrhythmia in an independent data set from UK Biobank study without a history of cardiovascular events (N=51 794; median follow‐up of 122 months) and SCD in patients with coronary artery disease from ARTEMIS (N=1872; median follow‐up of 60 months). In UK Biobank study, 220 (0.4%) individuals developed life‐threatening ventricular arrhythmias. TMV was significantly associated with life‐threatening ventricular arrhythmias (hazard ratio [HR] of 1.13 per SD increase [95% CI, 1.03–1.24]; P=0.009). In ARTEMIS, 34 (1.8%) individuals reached the primary end point. Patients with TMV ≥5 had an HR for SCD of 2.86 (95% CI, 1.40–5.84; P=0.004) with respect to those with TMV <5, independently from QRS duration, corrected QT interval, and left ventricular ejection fraction. TMV was not significantly associated with death from a cause other than SCD. Conclusions TMV identifies individuals at life‐threatening ventricular arrhythmia and SCD risk using a single‐beat single‐lead ECG, enabling inexpensive, quick, and safe risk assessment in large populations.